Rediscovering Aesthetics: Transdisciplinary Voices from Art History, Philosophy, and Art Practice - Halsall, Francis (Palo Alto, CA Stanford University Press, 2009)
Rediscovering Aesthetics brings together prominent international voices from art history, philosophy, and artistic practice to discuss the current role of aesthetics within and across their disciplines. Following a period in which theories and histories of art, art criticism, and artistic practice seemed to focus exclusively on political, social, or empirical interpretations of art, aesthetics is being rediscovered both as a vital arena for discussion and a valid interpretive approach outside its traditional philosophical domain. This volume is distinctive, because it provides a selection of significant but divergent positions. The diversity of the views presented here demonstrates that a critical rethinking of aesthetics can be undertaken in a variety of (possibly incompatible) ways. The contributions open a transdisciplinary debate from which a new field of aesthetics may begin to emerge.Contributors include: Claire Bishop, Diarmuid Costello, Paul Crowther, Arthur Danto, Nicholas Davey, Thierry de Duve, James Elkins, Francis Halsall, Michael Ann Holly, Julia Jansen, Michael Kelly, Robert Morris, Tony O'Connor, Peter Osborne, Adrian Piper, David Raskin, Carolee Schneemann, Richard Shiff, Wolfgang Welsch, and Richard Woodfield.
Keywords: 20th Century (1901-2000); 21st Century (2001-2100); Esthetics